Understanding the Spatial Conceptualization of Poverty: Implications for Sustainable Livelihoods in Africa (Global Journal of Human-Social Science, 2014)
Abstract not found
Keywords: poverty; spatial; sustainable livelihoods; urban poverty; rural poverty